Post Traumatic Stress Disorder Pada Korban Bencana - RM. Reza Imaduddin A (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2019)
Post-traumatic stress disorder is an disorder that can occur after experiencing or witnessing a terrible event, or torture with serious physical crimes, or threatening events. Disasters are traumatic events that can lead to various mental and physical health consequences. Victims of natural disasters experience physical and psychological stress, and previous research has shown that post-traumatic stress disorder (PTSD), depression, and other mental health problems can increase after the disaster. Large scale natural disasters that involve large numbers of people not only affect the mental health of victims, but also workers who carry out rescue and recovery tasks. Flashbacks restore emotions associated with traumatic events and make people very uncomfortable. PTSD has a large impact on individuals and society. There is evidence to suggest that, among anxiety disorders, PTSD is one of the most strongly associated with suicidal behavior. People with PTSD also struggle with interpersonal problems, parenting difficulties, and problems with household income, and have some mental illness and physical health